Clinical Profile of Thrombocytopenia Patients with Acute Febrile Illness in Tertiary Care Center Raipur, Chhattisgarh - Dr. Sarju Prasad; Dr. Manish Patil; Dr. D. P. Lakra; Dr. D. P. Lakra; Dr. Ajit Kumar; Dr. Archana Toppo (International Journal of Pharma and Bio Sciences, 2024)
Acute febrile illness with thrombocytopenia is a common condition associated with an increased risk of morbidity and mortality. India is a lower-middle-income country (LMIC), with approximately 70% of its population living in rural areas. Thrombocytopenia may be defined as a subnormal number of platelets in the circulating blood. Longer hospital stays in the intensive care unit (ICU), more bleeding events, more transfusions needed, and higher mortality are all associated with thrombocytopenia. Our study aims to observe clinical and laboratory parameters in patients with acute febrile illness with thrombocytopenia in a tertiary care centre. This cross-sectional study was carried out at a tertiary care teaching hospital. We included 125 patients with thrombocytopenia who were ≥18 years of age between March 2022 and December 2022. The patients were observed and followed up during their stay in the hospital, diagnoses were made, and bleeding manifestations and platelet transfusion requirements were recorded. Most patients were in the age group 26-35, with 31.2%. The male-to-female ratio in our study was 1.3:1. Apart from fever, the most common symptom was myalgia (65.6%). Dengue was diagnosed in most of the patients (56.8%). The platelet counts of <10000/ cum were observed in 22 patients, among which 14 showed bleeding manifestations. Acute kidney injury was the most common complication in 24.8% of patients, followed by Hepatitis in 14.4%. An early diagnosis and targeted therapy for the underlying cause of febrile thrombocytopenia and maintenance of platelet count and haemostatic function lead to an effective recovery.